BUSINESS MODEL OF INNOVATIVE PRODUCT STARTUP - B. Tokarev (Вестник университета)
The article presents the analysis of main problems associated with innovative product startup. Discussion has focused on the analysis of marketing solutions among all the variety of innovative startup problems. It has stated that marketing begins not from first sales, but much earlier, at the stages preceding the startup. The approaches to identification of first consumers of innovative product have analyzed. The principle based on the cyclic process for product creation, evaluation sales results and finding opportunities for its improvement has described. Particular attention has directed to the choice of innovative products pricing principles. Problems of innovation pricing have identified.